Association of blood-pressure time-in-therapeutic range with morbidity and mortality in hypertensive patients: a retrospective cohort study in the community setting - Tamara Alonso-Safont; Elena Polentinos-Castro; Isabel del-Cura-González; Amaia Bilbao-González; Jesus Martín-Fernández (BMC Public Health, 2026)
Abstract Background Hypertension is one of the leading modifiable risk factors for cardiovascular disease. This study assessed the association between good blood pressure control (GBPC), measured by time in therapeutic range (TTR) during the first year after hypertension diagnosis, and kidney or cardiovascular (K/CV) events and mortality in a large real-world cohort. Methods This population-based retrospective cohort included adults newly diagnosed with hypertension in primary care in Madrid, Spain, between 2007 and 2008, with no previous K/CV disease. Participants were identified from electronic medical records; outcomes were recorded until December 31, 2018, death, or deregistration. TTR during the first year was calculated using the indirect (iTTR; proportion of follow-up time within the BP target range) and direct (dTTR; proportion of BP measurements within the BP target range) methods. GBPC was defined as the highest TTR quartile (≥ 81% for iTTR and ≥ 67% for dTTR) or the last office BP measurement < 140/90 mmHg. Associations with mortality and K/CV events were evaluated using Cox regression models. Results A total of 38,002 patients were included (median age, 59 years [IQR, 49–69]; 53.9% women), with a median follow-up of 130.6 months (IQR, 123.1–137.3). During follow-up, 3,947 patients died (899 from K/CV causes), yielding an all-cause mortality rate of 8.24 per 10,000 person-months. A total of 11,727 K/CV events occurred, including 401 deaths. After adjustment for covariates, GBPC was associated with a 28% lower risk of all-cause mortality (95% CI, 5–45%) in patients diagnosed before 55 years (iTTR) and a 10% lower risk (95% CI, 0–20%) in those aged 55–74 years (iTTR and dTTR). GBPC was also associated with lower K/CV risk in patients aged < 55 years (11% [95% CI, 1–20%] for iTTR and 17% [95% CI, 8–25%] for dTTR) and 55–74 years (11% [95% CI, 6–16%] for iTTR and 10% [95% CI, 4–14%] for dTTR). No significant associations were observed at ≥ 75 years. Conclusion Good blood pressure control during the first year after diagnosis, defined using TTR and a BP target of < 140/90 mmHg, was associated with lower risks of mortality and K/CV events among patients diagnosed before age 75 years.